Effect of Garbha Samgari in Production for Healthy Child - Singh, Pankaj Kumar; Singh, Lalima; Verma, Mithilesh (International Research Journal of Ayurveda & Yoga, 2022)
Ayurveda is one of the most ancient systems of medicine in the world. At present time, the existence of everything has been proved practically and scientifically. So, Ayurveda needs a deep study and research for proving all the facts established by Acharya in ancient time. In Ayurveda, the concept of Garbha & Garbhotpatti is described systematically. Acharya have explained four important factors as Garbha Sambhav Samagri that is Ritu, Kshetra, Ambu and Beeja. These factors are very essential for conception. Infertility may occur if there is any abnormality in Garbha Sambhav Samagri. So, for a healthy and best offspring the factors concerned with conception must be in good qualities. The knowledge of Garbhotpatti helps to create suitable conditions for conception and healthy foetus also. This study will help to understand the normal and abnormal features of Garbha Sambhav Samagri in production of a healthy child.